2004
DOI: 10.1021/tx049939e
|View full text |Cite
|
Sign up to set email alerts
|

Arsenite Causes DNA Damage in Keratinocytes Via Generation of Hydroxyl Radicals

Abstract: Arsenic is an environmental and occupational toxin. Dermatologic toxicities due to arsenic exposure are well-documented and include basal cell and squamous cell carcinomas. However, the mechanism of arsenic-induced skin cancer is not well-understood. Recent studies indicate that arsenic exposure results in the generation of reactive oxygen species (ROS) and oxidative stress. Here, we examined the chemical nature of the specific ROS, studied the interrelationship among these species, and identified the specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
89
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(92 citation statements)
references
References 49 publications
(65 reference statements)
3
89
0
Order By: Relevance
“…Accumulating evidence suggests that oxidative stress occurs in response to arsenic exposure [5,6] and may be one factor in dermal arsenic carcinogenesis. Indeed, evidence of arsenic-induced oxidative DNA damage has been observed in cells [7][8][9][10][11][12], in rodents [13] and in humans [14].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence suggests that oxidative stress occurs in response to arsenic exposure [5,6] and may be one factor in dermal arsenic carcinogenesis. Indeed, evidence of arsenic-induced oxidative DNA damage has been observed in cells [7][8][9][10][11][12], in rodents [13] and in humans [14].…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic causes cellular toxicity by damaging the body's oxidative defense mechanisms [12].Chronic arsenic exposure causes excessive free radical generation in the body [13][14][15][16], Arsenic induced oxidative stress generates the superoxide radical and the hydroxyl radical primarily associated with mitochondria, microsomes and peroxisomes [17]. As a result, cells under oxidative stress display various dysfunctions due to lesions caused by reactive oxygen species (ROS) to lipids, proteins and DNA [18].…”
Section: Discussionmentioning
confidence: 99%
“…As for arsenic compounds, many reports have indicated that they increased oxidative DNA damage in cultured cells (6,7). For example, hydroxyl radical-induced oxidative DNA damage was generated in arsenic trioxide-treated keratinocyes (10). In addition, elevated levels of 8-OH-dG were observed in the urine of the patients with arsenic poisoning (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that the urinary 8-OH-dG level is increased with exposure to arsenic compounds (8,9). The DNA damage induced by arsenic compounds was extensively investigated, and the contributions of reactive oxygen species (ROS) and nitric oxide generated by arsenic compounds to the carcinogenic mechanisms have been suggested (10)(11)(12). However, the exact role of DNA damage in arsenic compound-related carcinogenesis is still unclear.…”
Section: Introductionmentioning
confidence: 99%